Repeated 5-aminolevulinic acid mediated sonodynamic therapy using magnetic resonance guided focused ultrasound in rat brain tumour models - Sheng-Kai Wu; Chia-Lin Tsai; Aisha Mir; Stuart L. Marcus; Kullervo Hynynen (Scientific Reports)
Abstract Sonodynamic therapy is an emerging therapeutic approach against brain tumours. However, the treatment scheme and ultrasound parameters have yet to be explored for clinical translation. Our study aimed to optimize ultrasound parameters for sonodynamic therapy (SDT) with 5-ALA as a sonosensitizing agent and to evaluate its therapeutic outcome on the rodent 9L gliosarcoma and the human U87 glioblastoma models. We stereotactically implanted brain tumour cells in rats and monitored tumour volume via MRI. SDT was conducted weekly using a 60 mg/kg dose of 5-ALA, injected intravenously 6 h before sonication. We used a driving frequency of 580 kHz with 0.75 MPa and evaluated the effect of different burst lengths to optimize ultrasound parameters. We also tested SDT against advanced-stage brain tumours to verify its efficacy further. Our results showed that a longer burst length could improve therapeutic outcomes. Tumour growth inhibition was established only in the first three weeks with 10 ms and 50 ms burst length sonication, but 86 ms burst length greatly improved the survival outcome. Therefore, the therapeutic efficacy is proportionate to the burst length and, thus, the total delivered energy. Repeated SDT using multiple targets to cover the entire tumour volume with optimal ultrasound parameters can achieve significant anti-tumour effects in both 9L and U87 models. Lastly, our results on late-stage tumour treatments showed that SDT can still provide prolonged survival. These promising findings demonstrate that repeated SDT using transcranial-focused ultrasound together with 5-ALA can optimize anti-tumour effects and even lead to complete clearance of the tumours. This weekly treatment with pulsed ultrasound sonication strategy is practical for future clinical translation.